The Problem of Democracy against the Background of the Theory of Origin and Authority in the Social Doctrine of the Church Fathers and St. Thomas Aquinas - Pawlikowski, Tomasz (Studia Theologica Varsaviensia, 2020)
"e modern social doctrine of the Catholic Church supports all of the abovementioned views with the exception that it treats some of its elements as the so-called “signs of the times” in which the creators of these views lived and wrote. "erefore, we cannot say that they became somehow time-barred. "ey have entered the tradition of the social doctrine of the Church. Similarly, one cannot reasonably claim that the basic theses of the socio-political theories of Saint Augustine or Saint "omas Aquinas are obsolete in philosophical terms. At the most, one can disagree with them or try to correct them. Nevertheless, it seems that there are no better analyses of the nature of authority and its origin from God. Considering these issues from the perspective of historical applications of the theories, especially the one coined by St. "omas, it is impossible not to notice the significant analogies of the reflections of Doctor Angelicus and the idea of a “nobles’ democracy” implemented in the First Polish Republic three hundred years later. It is also difficult to believe that a$er the creation of the scientific community of the Jagiellonian University in the fi$eenth century, they did not affect the minds of Polish politicians at a time when the foundations of this democracy were formed. Moreover, it seems that these considerations were widely applied in the centuries-old process of crystallizing other modern and contemporary democratic system.